COVID-19 impact and response by Canadian pain clinics: A national survey of adult pain clinics - Mary E. Lynch; Owen D. Williamson; Jillian C. Banfield (Taylor & Francis Group, 2020)
Background: As the result of public health authority responses to the COVID-19 pandemic, pain clinics have had to cease providing in-person appointments to reduce contact between patients and staff. Over the past decade, Canadians living with chronic pain have faced long waiting times for care within multidisciplinary pain clinics. We are concerned that ceasing in-person pain services exacerbates the daily hardships already faced by Canadians living with chronic pain. Aims: The aim of this study was to evaluate the impact of the COVID-19 pandemic on Canadian pain clinics, their responses, and changes to clinic practices that might be maintained when the pandemic is over. Methods: A survey of Canadian adult multidisciplinary pain clinics was conducted to determine impacts on medical and allied health care services and the strategies used to deliver care to patients during the COVID-19 pandemic. Results: Responses received from 17 adult pain clinics across Canada showed that adult multidisciplinary pain clinics had to cease or significantly reduce in-person patient contacts during the COVID-19 pandemic and responded by offering telehealth options. Despite their efforts, patients are waiting longer and have lost access to usual care. Increased levels of pain, stress, and medication use, particularly opioids and cannabinoids, were reported. Conclusions: Access to adaptable and innovative technologies, such as telehealth, can assist in the care of the one in five Canadians living with chronic pain during times of crises and must be included as a vital component of a comprehensive Canadian pain strategy.